Penerapan Metode RAD (Rapid Application Development) Pada Sistem Informasi Promosi dan Pemesanan Makanan Berbasis Website Studi Kasus Restoran Waroenk Anak Kuliahan - Aldisa, Rima Tamara (Building of Informatics, Technology and Science (BITS), 2021)
Traders food in the current era have an accurate online system to assess their merchandise. It is through promotion that consumers or customers become aware of the current business opportunities in the culinary field and can develop quickly. By continuing to develop, design, simulate and implement online. The design and flow of this application will be based on a website built using the RAD method to reduce or reduce the time required to create or design and implement it in four stages. The results of this application will issue outputs and results in the form of collaboration, restaurant background, information such as food menus and prices, addresses and locations of restaurants connected to google maps, how to order or place reservations and food, detailed results of food orders and sales reports. With the creation of this food promotion and ordering information system, it can help restaurant owners in promoting food menus and prices along with seeing the time, and making it easier for customers to find restaurant locations and customers in advance can order places and food menus in advance